A sampling of the manufacturing and distributing sectors of the Philippine Garments Export Industry its awareness of and reactions to changing trade policies (Quota phase-out, NAFTA / Carribbean Basin Initiative and US Rules of origin - Abayan, Maureen del Rosario
The Garments and Textile Export Board has been reporting and painting an alarming scenario for the Philippines' export condition which could be, to a large extent, based on the effects of trade policy changes. It is important therefore, to look into the awareness and reactions of the industry to critical changes like these. For the purposes of this study the following changes have been singled out: a) Quota phase-out, b) NAFTA/Caribbean Basin Initiative, and c) US Rules of Origin. Objectives were set to be both bi-focal and three pronged. It is bi-focal because it targets both the manufacturing and the distributing sectors of the industry. Also, it aimed to describe three things: 1) the awareness situation as of the interview period (last 2 months of 1996 up to 1st month of 1997; 2) the general reactions of the companies to the three trade policies identified; 3) the general effectivity of the coping mechanisms that may have been planned or set-up to adapt to possible negative repercussions that may come about. The research had fifteen respondents: five from trading or buying officers (distributing sector), and ten from the manufacturing sector. Sample sizes were purposely made unequal to roughly represent the actual difference in the number of manufacturing and distributing companies within the garment industry in the country. The five distributing companies sampled were taken from the Foreign Buyers Association of the Philippines while ten manufacturing companies were taken from the top 100 garment manufacturers in the Philippines according to the Garment and Textiles Export Board. All the companies sampled are located within and around the Metro Manila area. Most importantly they cater to the US market. The prepared questionnaire was personally administered to the respondents. (Data gathered were then collated and arranged according to certain factors considered in frequency distribution and then, they were presented in tabulated form.)The results showed that at the very least, perfunctory awareness among the companies interviewed is above average. There were both positive and negative expectations from the Quota phase-out while majority believed that the North American Free Trade Agreement (NAFTA/Carribean Basin Initiative (CBI) issue will have generally negative effects. Rules of Origin changes, on the other hand, will be barely felt by the sample group because it is limited to home textile products. As for the coping mechanism set-up, there were few, if any, that were specifically intended for the trade policy changes tackled by this study. General plans for improvement however, were enumerated by some interviewees. One of those mentioned was to improve technology in terms of equipment and knowhow which will in turn shorten lead time, increase efficiency and generally lower production cost. Another is training for personnel to be able to keep up with the technological advancement as well as improve job-related skills. However, since most of these plans are still on the drawing boards there could not be any discussion on how effective they have been.